Peptides Derived From S and N Proteins of Severe Acute Respiratory Syndrome Coronavirus 2 Induce T Cell Responses: A Proof of Concept for T Cell Vaccines - Lee, Yu-Sun; Hong, So-Hee; Park, Hyo-Jung; Lee, Ho-Young; Hwang, Ji-Yeon; Kim, Seo Yeon; Park, Jun Won; Choi, Kang-Seuk; Seong, Je Kyung; Park, Sang-In; Lee, Sang-Myeong; Hwang, Kyung-Ah; et al. (Frontiers in Microbiology, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that escape vaccine-induced neutralizing antibodies has indicated the importance of T cell responses against this virus. In this study, we highlight the SARS-CoV-2 epitopes that induce potent T cell responses and discuss whether T cell responses alone are adequate to confer protection against SARS-CoV-2; and describe the administration of 20 peptides with an RNA adjuvant in mice. The peptides have been synthesized based on SARS-CoV-2 spike and nucleocapsid protein sequences. Our study demonstrates that immunization with these peptides significantly increases the proportion of effector memory T cell population and IFN-γ-, IL-4-, TNF-α-, and granzyme B-producing T cells. Of these 20 peptides, four induce the generation of IFN-γ-producing T cells, elicit CD8+ T cell responses in a dose-dependent manner, and induce cytotoxic T lymphocytes that eliminate peptide-pulsed target cells in vivo. Although it is not statistically significant, these peptide vaccines reduce viral titers in infected hamsters and alleviate pulmonary pathology in SARS-CoV-2-infected human ACE2 transgenic mice. These findings may aid the design of effective SARS-CoV-2 peptide vaccines, while providing insights into the role of T cells in SARS-CoV-2 infection.